A composite method to identify desertification 'hotspots' and 'brightspots'. (14th April 2019) - Singh, Rimjhim Bhatnagar; Ajai,
Abstract: Desertification has become one of the greatest environmental concerns of our planet. Implementation of the action plans for arresting land degradation and for employing rehabilitation measures over a large spatial scale is not feasible due to the amount of time, effort, and cost involved. However, if the 'hotspots' the 'brightspots', and the 'potential areas' are identified, the task would be relatively easy. In this paper, a method is proposed to identify the pieces of degraded land with varying severity levels (in terms of 'hotspots', 'brightspots', and 'potential areas'), using Bowen ratio, land surface temperature (LST), R a, and Normalized Difference Vegetation Index (NDVI). Although the zone falls in the semiarid class, the microclimate analysis of the study area revealed high aridity. The combined analysis of LST, R a, and NDVI helped in identifying the areas susceptible to land degradation (particularly, salinization and water erosion). Analysis of the vegetation type and condition showed their variable roles towards the protection of soil from erosion, drought, and fire. Using these analyses together with the ecosystemic approach of Bowen ratio, 'hotspots', 'brightspots', and 'potential areas' were identified at the pixel level. For validation, Desertification Status Map was employed. The investigations revealed that around 49% of the study area falls under the category of 'hotspots' (with an error estimate of 13%) and another 49% as 'brightspots'. The findings revealed that instead of targeting the entire area for implementation of the mitigation measures with the same efforts, it would be better to focus on the specific pieces of land ('hotspots') to optimally utilize the available resources.